2003
DOI: 10.1073/pnas.2637013100
|View full text |Cite
|
Sign up to set email alerts
|

DNA-methyltransferase 1 mRNA is selectively overexpressed in telencephalic GABAergic interneurons of schizophrenia brains

Abstract: A down-regulation of reelin and glutamic acid decarboxylase (GAD) 67 mRNAs was detected in ␥-aminobutyric acid (GABA)ergic cortical interneurons of schizophrenia (SZ) postmortem brains (10), suggesting that the availability of GABA and reelin may be decreased in SZ cortex. In situ hybridization of the mRNA encoding for DNA-methyltransferase 1, which catalyzes the methylation of promoter CpG islands, shows that the expression of this mRNA is increased in cortical GABAergic interneurons but not in pyramidal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
213
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(236 citation statements)
references
References 43 publications
(48 reference statements)
19
213
1
3
Order By: Relevance
“…The development and function of the nervous system appears to be particularly sensitive to disruptions in epigenetic gene regulation, leading to syndromes associated with mental retardation (reviewed in Egger et al, 2004), as well as complex psychiatric disorders such as schizophrenia (Veldic et al, 2004;Grayson et al, 2005). The nervous system is unique in the remarkably complex patterning of the brain that must be established, while still maintaining a large degree of plasticity in order for the brain to respond to a changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…The development and function of the nervous system appears to be particularly sensitive to disruptions in epigenetic gene regulation, leading to syndromes associated with mental retardation (reviewed in Egger et al, 2004), as well as complex psychiatric disorders such as schizophrenia (Veldic et al, 2004;Grayson et al, 2005). The nervous system is unique in the remarkably complex patterning of the brain that must be established, while still maintaining a large degree of plasticity in order for the brain to respond to a changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…64 These authors suggest that targeting this deficit with inhibitors of histone deacetylases (HDAC), may reduce the DNMT upregulation via covalent modification of nucleosomal histone tails, potentially upregulating Reelin expression in schizophrenic brain. 64,66 Indeed, Veldic et al 67 have recently shown that mRNA for DNA-methyltransferase 1, which catalyzes the methylation of promoter CpG islands, is increased in cortical GABAergic interneurons but not in pyramidal neurons of schizophrenic brains. Despite these biochemical findings, two recent reports fail to report any association between Reln gene polymorphisms and schizophrenia.…”
mentioning
confidence: 99%
“…The expression of Dnmt3a is observed from late embryogenesis (E10) to adulthood with a peak during the early postnatal period; its expression declines to lower but detectable levels in the adult brain (Feng et al, 2005) with a reported biphasic increase in older humans (Siegmund et al, 2007). This nonconstitutive and regulated expression is supported by the observation that DNMT1 seems more highly expressed in the 'interneurons' of the cortex (GABA interneurons in the cerebral cortex, and granular cells in the cerebellar cortex) than the 'output' neurons, that is, pyramidal or Purkinje cells respectively (Veldic et al, 2004).…”
Section: Regulation Of Expressionmentioning
confidence: 86%
“…Interestingly, several studies have reported higher DNMT1 mRNA expression in schizophrenia post-mortem cortical and striatal GABAergic neurons (Veldic et al, 2004. DNMT1 expression was negatively correlated with schizophrenia candidate gene expression.…”
Section: Regulation Of Expressionmentioning
confidence: 96%
See 1 more Smart Citation